Implementation of Importance-Performance Analysis (IPA) for Improving Medical Students’ Quality of Service in Teaching Hospital - Siska Nia Irasanti; Ieva Baniasih Akbar; Yani Dewi Suryani (Universitas Islam Bandung, 2020)
One of the most relevant elements for improving the quality of an organization is the recognition of customer satisfaction and perceived quality of services. During their clerkship, medical students are required to work with different medical specializations in rotation and treat patients under the supervision of the attending physicians. The purpose of the study is to explore the medical students' quality of service using the importance-performance analysis (IPA) diagram that focused on the conformance level (CLi) between the actual service performance score and patient expectation score. This was a cross-sectional study involving 160 patients and patient caregivers at the Department of Pediatric of West Java Provincial Al-Ihsan Regional General Hospital Bandung, who was a purposive sampling method to participate in the study during January 2018. Results showed that the total CLi was less than 100%. The CLi scores for responsiveness, empathy, assurance, and reliability components were 84.57%, 84%, 83.56%, and 83.45%, respectively. It can be concluded that the services provided were good, but have not yet been able to meet the expectation of the patients. Overall, the IPA is useful to identify areas for strategic focus in improving the quality of services provided by medical students to help the hospital managers and faculty of medicine develop education management strategies. PENERAPAN IMPORTANCE-PERFORMANCE ANALYSIS (IPA) UNTUK MENINGKATKAN KUALITAS PELAYANAN MAHASISWA SELAMA KEPANITERAAN DI RUMAH SAKIT PENDIDIKANSalah satu elemen yang paling relevan untuk meningkatkan kualitas organisasi adalah mengetahui kepuasan dan kualitas layanan yang dirasakan oleh konsumen. Selama kepaniteraan, mahasiswa kedokteran diwajibkan untuk berotasi melalui berbagai spesialisasi medis dan merawat pasien di bawah pengawasan dokter. Tujuan penelitian ini mengetahui kualitas pelayanan mahasiwa kedokteran dengan menggunakan diagram importance-performance analysis (IPA) yang berfokus pada tingkat kesesuaian (Tki) antara skor kinerja layanan aktual dan skor harapan pasien. Penelitian ini merupakan penelitian cross-sectional yang melibatkan 160 pasien dan penunggu pasien di Departemen Ilmu Kesehatan Anak di RSUD Al-Ihsan Provinsi Jawa Barat Bandung dengan metode purposive sampling selama bulan Januari 2018. Hasil penelitian menunjukkan bahwa total Tki kurang dari 100%. Skor Tki untuk komponen respons, empati, assurance, dan reliabilitas masing-masing adalah 84,57%, 84%, 83,56%, dan 83,45%. Dapat disimpulkan bahwa faktor layanan yang diberikan baik, tetapi belum memenuhi harapan pasien. Meskipun demikian, IPA berguna untuk mengidentifikasi area untuk fokus strategis dalam meningkatkan kualitas layanan yang diberikan mahasiswa kedokteran untuk membantu manajer rumah sakit dan fakultas kedokteran mengembangkan strategi manajemen pendidikan.